Navigating online learning for citizenship education through parenthood in the digital era - Halimah, Lili; Romlah, Oom Yomi; Heryani, Heni; Setiawati, Lilis (Universitas Negeri Yogyakarta, 2024)
During the pandemic, learning policies have transformed face-to-face to online-based learning. Technology and information play a crucial role in learning infrastructure, sources of teaching materials, tools, learning facilities, and learning media. The activeness of parents in accompanying children dramatically influences the effectiveness of learning activities, which ultimately contributes to maximum results. This research explored the characteristics of parental assistance and the problems that arose in online learning of Citizenship Education subjects in Jaya Mekar Padalarang Village. The results show that the home learning policy is considered burdensome by parents. Some reasons include difficulty managing time between working and guiding children, lack of adequate communication facilities, difficulty understanding lesson material, and inability to use technological devices. In this context, finding solutions or strategies that can help parents overcome these challenges is important. However, it's crucial to stress that with the right support and training, parents can significantly improve their support for their children's online learning. This effort can increase parents' active participation in supporting their children's online learning and inspire a positive change in the online education landscape.